Pengaruh Inventarisasi Aset, Penilaian Aset Dan Legal Audit Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Elisabeth Emarlin Ruda; Wilhelmina Mitan; Yoseph Darius P.Rangga (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This research aimed to determine the effect of asset inventory, aset valuation and legal audit on the quality of local government financial statements in Sikka Regency. The method used a quantitative explanatory. The populations in this research were all employees who were divided into several divisions with a total of 53 employees. The sampling technique employed a saturated sampling technique with a sample size of 53 respondents. In this research, the type of data used was primary data. Data collection procedures used a questionnaire measured on a likert scale. The data analysis techinique used multiple linear analysis methods with descriptive statistical tests, data quality tests, classical assumption tests, and hypothesis testing. The results indicated that partially and simultaneously asset inventory, asset valuation and legal audit had a positive effect on the quality of local government financial statements in Sikka Regency.